Synergistic Effect in Green Extraction of Noble Metals and Its Consequences. Issue 24 (29th June 2017) - Nag, Abhijit; Baksi, Ananya; Krishnapriya, K. C.; Gupta, Soujit Sen; Mondal, Biswajit; Chakraborty, Papri; Pradeep, Thalappil
Abstract : Extraction of silver into water occurs from its apparently inert metal surface by the simple carbohydrate glucose. Here we show that there are large synergistic effects in the extraction process, which results in ca. 45 times larger leaching with specific molecules, when used along with glucose. While glucose (1 g) alone can extract ca. 650 ppb of silver from the metal, 60 mg of it extracts ca. 30000 ppb in a combination with 200 mg of glutathione (GSH) under similar experimental conditions of 70 °C and an extraction time of 7 d, in deionized (DI) water (200 mL). This enhancement is similar when glucose is replaced with cyclodextrin (CD). This enhanced concentration of silver in solution enables the formation of the silver clusters protected with glutathione and cyclodextrin, Ag20 (SG)15 CD 3–, in the presence of a reducing agent. A similar extraction for copper leads to excessive leaching, and typical concentrations are even higher than the solubility limit of the copper–glutathione complex. As a result, these complexes are precipitated. This synergistic extraction is observed for zinc and stainless steel as well. Enhanced extraction is a result of the formation of complexes of metals with glutathione and the consequent leaching of the complex into solution as well as the stabilization of the complex by inclusion complexation with cyclodextrin. Enhanced leaching in the presence of glucose is mostly due to simultaneous complexation with glucose as well as glutathione. The science presented may be used for the green extraction of different metals and could be a new potential top‐down approach for metal cluster synthesis. This may also be useful for green and sustained leaching of minerals into water to regulate its quality. Abstract : A large amount of silver goes into water from metallic silver by the process of extraction, which enables the synthesis of the noble‐metal cluster Ag20 (SG)15 CD 3– in water [CD = γ‐cyclodextrin, SG = glutathione thiolate (GSH–H)]. The surface of silver foil after extraction was examined thoroughly. Blade‐like structures were found when MBA (mercaptobenzoic acid) was used in place of GSH.